Tinjauan Hukum Islam terhadap Teknologi Bayi Tabung dan Surrogacy: Kajian Normatif Berdasarkan Maqasid al-Syari’ah - Nur Aksa, Fauzah; Herinawati; Tahmid, Muhammad; Widia, Siska Mona (LP2M IAIN Palopo, 2025)
The advancement of modern reproductive technologies, such as in vitrofertilization (IVF) and surrogacy, has provided medical alternatives for couples facing infertility issues. Despite their benefits, these practices raise significant concerns from the perspective of Islamic law, particularly regarding lineage (nasab), the sanctity of the womb, and the protection of offspring. This study aimsto analyze the permissibility of IVF and surrogacy within Islamic jurisprudenceusing a normative approach, and to assess their compatibility through the lens ofmaqasid al-shari’ah (the higher objectives of Islamic law). This research employs a normative qualitative method, drawing upon classical and contemporary Islamic jurisprudential literature, fatwas from recognized Islamic legal institutions (such as the Indonesian Ulema Council and the International Islamic Fiqh Academy), and the theoretical framework of maqasid al-shari’ah. The study finds that IVF is permissible in Islamic law as long as it occurs within a lawfulmarital relationship and does not involve third-party donors. On the other hand, all forms of surrogacy—whether involving a genetic link to the surrogate or not—are prohibited (haram) due to their potential to compromise lineage, exploit women’s bodies, and violate the sanctity of the reproductive process. The findings reaffirm that Islamic law, through the objectives of maqasid al-shari’ah, places a strong emphasis on the preservation of lineage (hifz al-nasl) and the integrity ofthe family unit. Thus, modern reproductive technologies are only acceptable whenthey align with these fundamental ethical and legal principles. This study contributes to the development of contemporary Islamic jurisprudence and serves as a reference for formulating religiously appropriate policies in the face of evolving medical advancements. Keywords: Islamic Law, In Vitro Fertilization, Surrogacy, Maqasid al-Shari’ah, Lineage, Modern Reproduction.